2013
DOI: 10.3109/19390211.2013.822452
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofSpirulina(Arthrospira) Supplementation on the Immune Response to Tetanus Toxoid Vaccination in a Mouse Model

Abstract: The aim of this study was to investigate whether Spirulina (Arthrospira) supplementation could enhance the immune response to tetanus toxoid (TT) vaccine in a mouse model. Vaccination of TT was performed on day 7 and 21 in mice fed daily with Spirulina (50 and 150 mg/kg body weight). Both Spirulina supplementation and TT vaccination did not significantly affect body weight gain of the mice. Supplementation of Spirulina significantly enhanced IgG level (p = .01) after the first but not after the second TT vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…However, the response antibody response was faster and stronger in the Spirulina group (P < 0.05). Similarly, one previous study in mice demonstrated an increased tetanus toxoid vaccine response 21 days post vaccination, in mice orally administered with Spirulina powder for 7 days prior to, and thereafter, vaccination compared to control mice who did not receive Spirulina (46). We have previously used co-incident vaccination protocols with dietary manipulations to understand how a given diet could influence systemic immunity as vaccine responses are a relevant biomarkers of an immunological response to challenge (23,24), and can be interpreted as a surrogate marker of a typical immune response to infection (47).…”
Section: Discussionmentioning
confidence: 56%
“…However, the response antibody response was faster and stronger in the Spirulina group (P < 0.05). Similarly, one previous study in mice demonstrated an increased tetanus toxoid vaccine response 21 days post vaccination, in mice orally administered with Spirulina powder for 7 days prior to, and thereafter, vaccination compared to control mice who did not receive Spirulina (46). We have previously used co-incident vaccination protocols with dietary manipulations to understand how a given diet could influence systemic immunity as vaccine responses are a relevant biomarkers of an immunological response to challenge (23,24), and can be interpreted as a surrogate marker of a typical immune response to infection (47).…”
Section: Discussionmentioning
confidence: 56%
“…The phycocyanin in spirulina increases biological activity against infectious diseases by maintaining the function of the mucosal immune system and reducing allergic inflammation by suppressing specific antibodies, and injecting it produces IgA antibodies. Spirulina polysaccharide also activates innate immune cells and increases antibodies [ 72 ]. The polysaccharides and phycocyanins in spirulina help to both increase the number of antigens through physical activity and increase the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The prebiotic component of the synbiotic intervention we describe was a formulation comprised of (1) spirulina, which is derived from the filamentous cyanobacterium Arthrospira platensis and has reported prebiotic, antioxidant, and immunomodulatory effects (Neyrinck et al, 2017;Finamore et al, 2017;Chu et al, 2013); (2) amaranth grain, a pseudo-cereal consumed in many societies over the course of millennia, rich in a variety of antioxidants, vitamins, and essential amino acids (Gorinstein et al, 2007;Nimbalkar et al, 2012) and associated with a variety of reported health benefits (Huerta-Ocampo and Barba de la Rosa, 2011); (3) flaxseed, a rich source of fiber and u-3 fatty acids, that has been shown in preclinical models to alter gut microbial ecology and modulate enteroendocrine cell gene expression (Ar-ora et al, 2019); and (4) a set of micronutrients with immunomodulatory properties (reviewed in Maggini et al, 2018). The probiotic component of the synbiotic consisted of a consortium of five bacterial strains; these strains were identified from studies involving co-housing gnotobiotic mice with post-SAM MAM donor microbiota that conveyed discordant responses to oral CT vaccination and tracking how invasion of taxa from one community to another could enhance vaccine responses.…”
Section: Introductionmentioning
confidence: 99%